Profil Pengelolaan Obat dan Ketersediaan Obat - Kunnu, Hasbi; Rahem, Abdul; Utami, Wahyu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aimed to determine the profile of drug management and the availability of drugs hinge on 40 items of national indicator drugs at Enrekang’s Public Health Centers. This research method uses an observational descriptive study was conducted at a total of 14 public health centers in Enrekang Regency. A data collection sheet for the availability of 40 national indicator drug items in 2021 and an observational sheet were used as the research instrument. This study found that most of the public health centers in Enrekang Regency managed their drugs in the good category with a percentage of planning at 64.3%, procurement at 100%, reception at 100%, storage at 57.1%, distribution at 71.4%, destruction and withdrawal at 92.9%, control at 71.4%, administration of recording and reporting at 57.1%. Based on category, the availability percentage of 40 national indicator drug items at Enrekang’s Public Health Centers was safe at 56%, empty at 4.4%, less at 10.5%, and excess at 29.1%. In conclusion, most of the public health centers in Enrekang Regency managed their drugs in the good category, the availability of drugs in Enrekang’s Public Health Centers with a safe category is only 56%. Keywords: Drug Availability, Drug Management, Public Health Center